ANSIEDAD Y COMPORTAMIENTO EN ESTUDIANTES DE EDUCACIÓN GENERAL BÁSICA DE LA UNIDAD EDUCATIVA “COMBATIENTES DE TAPI” RIOBAMBA 2016-2017. - Vicuña López, Joseline Silvana (2019)
The research was conducted in the Educational Unit "Tapi Fighters" located in the province of Chimborazo in the school year 2016 - 2017, students of the Third Year of General Basic Education participated. The purpose was to determine how anxiety affected behavior in the students' classroom, the identification of anxiety traits as well as the identification of behavioral traits. The work was justified because it has a social value and shows a relationship between anxiety and behavior of children in the classroom. It was based on John Guilles' theory of child anxiety and the Basc behavior assessment system. The research was approached from the non-experimental research design with the perspective according to the type of descriptive and exploratory study. The population used for the research was 99 students from the three levels of the Third Year of Basic General Education; the psychological reagents of the Infantile Anxiety Scale were used, consisting of twenty questions and the behavioral assessment system consisting of 146 questions. . The processing of the data information allowed us to determine the relationship between childhood anxiety and behavior. This allowed us to reach the following conclusion that shows that Anxiety affects the behavior of children in the classroom because in the research there are high rates of children with traits of bad behavior, causing a high level of anxiety in them.